Literature Is Important To Understand Learning Nutritional Levels To Increase Kindergarten School Children's Thinking Power - Sari Rahmadani, Fauza; Bayu Dani Nandiyanto, Asep (Riviera Publishing, 2022)
The purpose of this study was to find out how much nutrition is owned by children in TK NURUL ATHFAL school, the method used is learning using powerpoint media in the form of pictures. Teaching students are required to listen, dare to ask and answer questions that have been given to the teacher, and conduct joint discussions. Parents were given a pretest via Google from before the learning activity started and a posttest after the learning activity. The understanding and success of the student learning process that filled out the parents of the students with 20 pretest and posttest questions. The learning was carried out by 30 students at the NURUL ATHFAL Kindergarten school in the city of East Jakarta, Indonesia, this learning process was carried out online using the zoom meeting media. The results of this study showed that students can know healthy food and balanced nutrition. This is evidenced by the increase in the pretest and posttest by 20 questions to parents, some students who have more good nutrition than poor nutrition. this shows that learning is successful because the material that the teacher gives to students can be very understanding and active in learning because it can attract students' interest by using media songs that stimulate student interest, although in the posttest and pretest sections that are filled in by the parents of students there are less This research can provide information that parents already understand nutritional levels to improve the thinking power of school children and parents who fill out the questionnaire will seek to understand nutritional levels in depth and will try to apply them to their children in detail.